2005
DOI: 10.1002/chem.200401294
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitosis by Glycopeptide Dendrimer Conjugates of Colchicine

Abstract: Glycopeptide dendrimers have been prepared bearing four or eight identical glycoside moieties at their surface (beta-glucose, alpha-galactose, alpha-N-acetyl-galactose, or lactose), natural amino acids within the branches (Ser, Thr, His, Asp, Glu, Leu, Val, Phe), 2,3-diaminopropionic acid as the branching unit, and a cysteine residue at the core. These dendrimers have been used as drug-delivery devices for colchicine. Colchicine was attached to the dendrimers at the cysteine thiol group through a disulfide or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…Each amino acid would be utilized only twice during assembly of the combinatorial dendrimer library in two defined positions in successive branches (Figure 1). In this manner, any amino acid would occur with a relative abundance of 0, 1, 2, or 3, corresponding to either its absence (0) or its presence in the lower branch (1), the higher branch (2), or in both branches (3). The information from amino acid analysis would be redundant since the presence of any amino acid at a given position would be confirmed by the absence of the other amino acids at that position.…”
Section: Design Of the Peptide Dendrimer Combinatorial Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…Each amino acid would be utilized only twice during assembly of the combinatorial dendrimer library in two defined positions in successive branches (Figure 1). In this manner, any amino acid would occur with a relative abundance of 0, 1, 2, or 3, corresponding to either its absence (0) or its presence in the lower branch (1), the higher branch (2), or in both branches (3). The information from amino acid analysis would be redundant since the presence of any amino acid at a given position would be confirmed by the absence of the other amino acids at that position.…”
Section: Design Of the Peptide Dendrimer Combinatorial Librarymentioning
confidence: 99%
“…1 We are investigating peptide dendrimers constituted of alternating sequences of proteinogenic -amino acid and diamino acid building blocks as artificial protein models for catalysis 2 and drug delivery. 3 Natural proteins are the products of evolution, which selects functional sequences from a large genetically encoded repertoire of linear amino acid combinations by mutation and selection steps. Due to the linear nature of polypeptides, natural evolution must select amino acid sequences for both folding and function.…”
Section: Introductionmentioning
confidence: 99%
“…However, while natural proteins are structurally well understood, the structural and functional properties of these branched peptide-dendrimer analogues remain largely unexplored. In our efforts to explore this class of protein analogues, we have shown that screening of combinatorial libraries leads to peptide dendrimers with various functions, [4] such as catalysis of ester hydrolysis [5] and aldol reactions, [6] drug delivery, [7] biofilm inhibition mediated by lectin binding, [8] and programmed proteolysis. [9] We recently reported the identification of dendrimer B1 (Table 1) as a simple model for cobalamin transport proteins by screening of a peptide-dendrimer combinatorial library and structural optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The control of proteolysis by topology provides a novel possibility to tune the biological properties of peptide dendrimers not available in linear peptides, and should be generally useful for their use as functional biomolecule analogues, for example, in the context of drug delivery applications. [16] …”
Section: Introductionmentioning
confidence: 97%